Implementasi Self Determination Rights dan Kedaulatan Negara di Indonesia - Maryati B (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2018)
The success of the rights to self determination affects state sovereignty, in contrast to the successful use of the rights of self determination. This study collects literature materials through the study of textbooks and access the internet to obtain data and use qualitative descriptive methods to analyze data and penguliisannya. The question is: Can self-determination rights, especially rights to self-determination, be used at any time or in any country at the present moment, after colonialism is almost erased on earth? After Indonesia ratified the International Covenant on Civil and Political Rights and the International Covenant on Economic, Social and Cultural Rights in December 2005, are the Indonesian people free to use self-determination rights, both of which are rights to self determinants or rights of self determination? The rights of self-determination are also common, but in Indonesia it failed to transform the unitary state into a federation in 1999. With the ratification of the two Covenants, the people of Indonesia are not free to use rights to self-determination as well as the rights of self-determination because in both ratifying laws , Law Number 11 Year 2005 and Law Number 12 Year 2005 stipulated that the first article of the Covenant was declaration in the sense of exclusion of its ratification including the right to regulate all its resources and resources, so that ratified only other articles other than article 1 If there is also the use of the right to self-determination, there is no legal basis or legality in Indonesia.